Nano-silica-based heavy metal soil remediation agent and preparation method thereof
By using nanosilia-based chelating agents in soil repair agents and combining cellulose and modifiers to treat them, the problems of high cost and poor results of existing soil repair agents are solved, and efficient repair of heavy metals in soil is achieved.
Patent Information
- Application Number
- CN202411855118.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing soil repair agents are costly and it is difficult to effectively reduce the mobility and bioavailability of heavy metals in the soil.
The nanosilica-based chelating agent is used to treat cellulose alkali liquid to form a nanosilia-cellulose composite powder, and is modified by 3-aminopropyltriethoxysilane and tannic acid to improve the chelating property of the chelating agent.
It significantly reduces the content of effective lead and arsenic in the soil, reduces the toxicity of pollutants to the soil, and achieves the effect of soil repair.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of soil remediation, and in particular to a nano-silicon dioxide-based heavy metal soil remediation agent and a preparation method thereof. Background Art
[0002] At present, with the rapid increase of industrialization and human activities, heavy metal pollution in soil has become one of the most concerned issues in the world. In response to the serious soil pollution problem, the cost of the passivating agents currently used is relatively high, making the cost of soil heavy metal remediation huge. Therefore, environmentally friendly remediation agents based on cheap materials have become a hot topic in the academic community. Heavy metal ions in soil are mainly fixed through adsorption, precipitation, surface complexation, ion exchange, oxidation-reduction and other effects, thereby reducing mobility and bioavailability in the soil, and achieving the purpose of repairing heavy metal ions in the soil. Summary of the invention
[0003] To this end, the present invention provides a nano-silica-based heavy metal soil remediation agent, comprising a silica-based chelating agent, attapulgite, potassium dihydrogen phosphate and potassium humate, wherein the preparation method of the silica-based chelating agent is:
[0004] (1) preparing a dilute sodium hydroxide solution; adding cellulose and ethylene glycol to ethanol to prepare an alcohol suspension, stirring the alcohol suspension, and then adding the dilute sodium hydroxide solution to the alcohol suspension under stirring, continuing to stir for more than 3 hours after the addition is completed, and then separating the solid and the liquid, washing the solid phase with deionized water until the washed liquid is neutral, and drying at 60±5° C. for more than 5 hours to obtain pretreated cellulose;
[0005] (2) preparing an ethanol solution of tetraethyl orthosilicate; adding the pretreated cellulose, glycine, and cyclohexane into deionized water to prepare a mixed solution, heating the mixed solution to 60±5° C. in a water bath, and then adding γ-aminoethylaminopropyltrimethoxysilane under stirring. After the addition is completed, stirring is carried out at a constant temperature of 60±5° C. for 20 to 30 minutes. Then, the ethanol solution of tetraethyl orthosilicate is added under stirring. After the addition is completed, stirring is carried out at a constant temperature of 60±5° C. for more than 1 hour, solid-liquid separation is performed, the solid phase is washed with deionized water for more than 3 times, and dried at 60±5° C. for more than 5 hours to obtain a silica-based powder;
[0006] (3) adding the silica-based powder to toluene and stirring for more than 10 minutes to obtain a toluene suspension; heating the toluene suspension in a water bath to 80±5° C. for insulation, then adding 3-aminopropyltriethoxysilane to the toluene suspension under stirring, and continuing to stir at a constant temperature of 80±5° C. for more than 3 hours after the addition is completed, condensing and refluxing during the constant temperature process; after the stirring is completed, the solid-liquid separation is completed, the solid phase is washed with ethanol for more than 3 times, and dried at 60±5° C. for more than 5 hours to obtain an aminated powder;
[0007] (4) preparing an aqueous solution of tannic acid; preparing an aqueous solution of glutaraldehyde, immersing the aminated powder in the aqueous solution of glutaraldehyde, heating in a water bath to 37±3° C., stirring at a constant temperature for more than 2 hours, and then adding the aqueous solution of tannic acid under stirring. After the addition is completed, continue to stir at a constant temperature of 37±3° C. for more than 5 hours, then separate the solid and liquid, wash the solid phase with deionized water for more than 3 times, and dry at 60±5° C. for more than 5 hours to obtain the silica-based chelating agent.
[0008] Furthermore, the components of the nano-silica-based heavy metal soil remediation agent are calculated by weight as follows: 50 parts of silica-based chelating agent, 40-50 parts of attapulgite, 10-14 parts of potassium dihydrogen phosphate, and 6-8 parts of potassium humate.
[0009] Furthermore, in the step (1), the mass percentage of sodium hydroxide in the dilute sodium hydroxide solution is 5% to 6%, and the solvent is water; the mass ratio of cellulose and ethylene glycol added to ethanol to form an alcohol suspension is cellulose:ethylene glycol:ethanol=6-7:2-10:50; the volume ratio of adding the dilute sodium hydroxide solution to the alcohol suspension is alcohol suspension:dilute sodium hydroxide solution=1:1.2-1.5.
[0010] Furthermore, in the step (2), in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 5% to 6%, and the solvent is ethanol; the mass ratio of the pretreated cellulose, glycine, and cyclohexane added to the deionized water is pretreated cellulose: glycine: cyclohexane: deionized water = 3 to 4: 0.1 to 0.2: 5 to 8: 100; the volume ratio of γ-aminoethylaminopropyltrimethoxysilane and the ethanol solution of tetraethyl orthosilicate added to the mixed solution is mixed solution: γ-aminoethylaminopropyltrimethoxysilane: ethanol solution of tetraethyl orthosilicate = 25 to 30: 1 to 3: 100.
[0011] Furthermore, in the step (3), the mass ratio of the silica-based powder added to toluene is silica-based powder: toluene = 1:50-100; the volume ratio of the added 3-aminopropyltriethoxysilane to the toluene suspension is 3-aminopropyltriethoxysilane: toluene suspension = 0.3-0.5:50.
[0012] Furthermore, in the step (4), the concentration of tannic acid in the aqueous solution of tannic acid is 40-50 mg / mL, and the solvent is water; the mass percentage of glutaraldehyde in the aqueous solution of glutaraldehyde is 5%-6%, and the solvent is water; the mass ratio of the aminated powder, the aqueous solution of glutaraldehyde and the aqueous solution of tannic acid is aminated powder: aqueous solution of glutaraldehyde: aqueous solution of tannic acid = 1-2:50:10-15.
[0013] The beneficial effect of the present invention is that the soil remediation agent prepared by the method of the present invention has a good remediation effect on the polluting elements lead and arsenic in the soil, can significantly reduce the content of effective lead and effective arsenic, and reduce the toxicity of pollutants to the soil. The present invention first treats cellulose with alkali solution to reduce the crystallinity and polymerization degree of cellulose, improve the dispersibility, and at the same time form a large number of hydroxyl groups on the surface of cellulose, and subsequently form a composite powder of nano-silicon dioxide-cellulose, which on the one hand improves the specific surface area and porosity of the matrix powder and improves the adsorption of the material, and on the other hand forms macromolecular groups and active functional groups on the surface of the matrix powder, improves the chelation of the matrix and facilitates the subsequent further modification of the powder. Afterwards, 3-aminopropyltriethoxysilane is used to convert the hydroxyl groups on the surface of the powder into amino groups, and then tannic acid modification is performed, which can significantly improve the chelation of the silica-based chelating agent to the polluting ions, form a stable chelate, reduce the content of free polluting ions in the soil, and play a role in soil remediation. DETAILED DESCRIPTION
[0014] The present invention will be further described below in conjunction with the embodiments.
[0015] Example 1
[0016] A nano-silica-based heavy metal soil remediation agent comprises a silica-based chelating agent, attapulgite, potassium dihydrogen phosphate and potassium humate, wherein the components are as follows by weight: 50 parts of silica-based chelating agent, 40 parts of attapulgite, 10 parts of potassium dihydrogen phosphate and 6 parts of potassium humate; the raw materials are uniformly mixed to obtain the soil remediation agent; wherein the preparation method of the silica-based chelating agent is as follows:
[0017] (1) preparing a dilute sodium hydroxide solution, wherein the mass percentage of sodium hydroxide in the dilute sodium hydroxide solution is 5%, and the solvent is water; adding cellulose and ethylene glycol to ethanol to prepare an alcohol suspension, wherein the mass ratio of cellulose and ethylene glycol added to ethanol to prepare the alcohol suspension is cellulose: ethylene glycol: ethanol = 6:2:50; stirring the alcohol suspension, and then adding the dilute sodium hydroxide solution to the alcohol suspension under stirring, wherein the volume ratio of the dilute sodium hydroxide solution added to the alcohol suspension is alcohol suspension: dilute sodium hydroxide solution = 1:1.2; after the addition is completed, stirring is continued for 3 hours, and then solid-liquid separation is performed, and the solid phase is washed with deionized water until the washed liquid is neutral, and dried at 60° C. for 5 hours to obtain pretreated cellulose;
[0018] (2) preparing an ethanol solution of tetraethyl orthosilicate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 5%, and the solvent is ethanol; adding the pretreated cellulose, glycine, and cyclohexane into deionized water to prepare a mixed solution, wherein the mass ratio of the pretreated cellulose, glycine, and cyclohexane added to the deionized water is pretreated cellulose: glycine: cyclohexane: deionized water = 3:0.1:5:100; heating the mixed solution to 60° C. in a water bath and then adding γ-aminoethylaminopropyl trimethoxysilane, after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 20 minutes, and then the ethanol solution of tetraethyl orthosilicate is added under stirring, and the volume ratio of γ-aminoethylaminopropyl trimethoxysilane and the ethanol solution of tetraethyl orthosilicate added to the mixed solution is mixed solution: γ-aminoethylaminopropyl trimethoxysilane: ethanol solution of tetraethyl orthosilicate = 25:1:100; after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 1 hour, solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and dried at 60° C. for 5 hours to obtain a silica-based powder;
[0019] (3) adding the silica-based powder to toluene, wherein the mass ratio of the silica-based powder to toluene is 1:50; stirring for 10 min to obtain a toluene suspension; heating the toluene suspension to 80° C. in a water bath to keep it warm, and then adding 3-aminopropyltriethoxysilane to the toluene suspension under stirring, wherein the volume ratio of the added 3-aminopropyltriethoxysilane to the toluene suspension is 0.3:50; after the addition is completed, stirring is continued at a constant temperature of 80° C. for 3 h, and condensation and reflux are performed during the constant temperature process; after the stirring is completed, solid-liquid separation is performed, the solid phase is washed with ethanol 3 times, and dried at 60° C. for 5 h to obtain an aminated powder;
[0020] (4) preparing an aqueous solution of tannic acid; in the aqueous solution of tannic acid, the concentration of tannic acid is 40 mg / mL, and the solvent is water; preparing an aqueous solution of glutaraldehyde, in the aqueous solution of glutaraldehyde, the mass percentage of glutaraldehyde is 5%, and the solvent is water; soaking the aminated powder in the aqueous solution of glutaraldehyde, heating it to 37° C. in a water bath, stirring at constant temperature for 2 hours, and then adding the aqueous solution of tannic acid under stirring, the mass ratio of the aminated powder, the aqueous solution of glutaraldehyde and the aqueous solution of tannic acid being aminated powder: aqueous solution of glutaraldehyde: aqueous solution of tannic acid = 1:50:10; after the addition is completed, stirring is continued at constant temperature of 37° C. for 5 hours, and then solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 60° C. for 5 hours to obtain the silica-based chelating agent.
[0021] Example 2
[0022] A nano-silica-based heavy metal soil remediation agent comprises a silica-based chelating agent, attapulgite, potassium dihydrogen phosphate and potassium humate, wherein the components are as follows by weight: 50 parts of silica-based chelating agent, 45 parts of attapulgite, 12 parts of potassium dihydrogen phosphate and 7 parts of potassium humate; the raw materials are uniformly mixed to obtain the soil remediation agent; wherein the preparation method of the silica-based chelating agent is as follows:
[0023] (1) preparing a dilute sodium hydroxide solution, wherein the mass percentage of sodium hydroxide in the dilute sodium hydroxide solution is 5%, and the solvent is water; adding cellulose and ethylene glycol to ethanol to prepare an alcohol suspension, wherein the mass ratio of cellulose and ethylene glycol added to ethanol to prepare the alcohol suspension is cellulose: ethylene glycol: ethanol = 6:5:50; stirring the alcohol suspension, and then adding the dilute sodium hydroxide solution to the alcohol suspension under stirring, wherein the volume ratio of the dilute sodium hydroxide solution added to the alcohol suspension is alcohol suspension: dilute sodium hydroxide solution = 1:1.3; continuing to stir for 3 hours after the addition is completed, and then separating the solid and liquid, washing the solid phase with deionized water until the washed liquid is neutral, and drying at 60° C. for 5 hours to obtain pretreated cellulose;
[0024] (2) preparing an ethanol solution of tetraethyl orthosilicate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 5%, and the solvent is ethanol; adding the pretreated cellulose, glycine, and cyclohexane into deionized water to prepare a mixed solution, wherein the mass ratio of the pretreated cellulose, glycine, and cyclohexane added to the deionized water is pretreated cellulose: glycine: cyclohexane: deionized water = 3:0.1:6:100; heating the mixed solution to 60° C. in a water bath and then adding γ-aminoethylaminopropyl trimethoxysilane, after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 20 minutes, and then the ethanol solution of tetraethyl orthosilicate is added under stirring, and the volume ratio of γ-aminoethylaminopropyl trimethoxysilane and the ethanol solution of tetraethyl orthosilicate added to the mixed solution is mixed solution: γ-aminoethylaminopropyl trimethoxysilane: ethanol solution of tetraethyl orthosilicate = 25:2:100; after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 1 hour, solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and dried at 60° C. for 5 hours to obtain a silica-based powder;
[0025] (3) adding the silica-based powder to toluene, wherein the mass ratio of the silica-based powder to toluene is 1:50; stirring for 10 min to obtain a toluene suspension; heating the toluene suspension to 80° C. in a water bath to keep it warm, and then adding 3-aminopropyltriethoxysilane to the toluene suspension under stirring, wherein the volume ratio of the added 3-aminopropyltriethoxysilane to the toluene suspension is 0.4:50; after the addition is completed, stirring is continued at a constant temperature of 80° C. for 3 h, and condensation and reflux are performed during the constant temperature process; after the stirring is completed, solid-liquid separation is performed, the solid phase is washed with ethanol 3 times, and dried at 60° C. for 5 h to obtain an aminated powder;
[0026] (4) preparing an aqueous solution of tannic acid; in the aqueous solution of tannic acid, the concentration of tannic acid is 40 mg / mL, and the solvent is water; preparing an aqueous solution of glutaraldehyde, in the aqueous solution of glutaraldehyde, the mass percentage of glutaraldehyde is 5%, and the solvent is water; soaking the aminated powder in the aqueous solution of glutaraldehyde, heating it to 37° C. in a water bath, stirring at constant temperature for 2 hours, and then adding the aqueous solution of tannic acid under stirring, the mass ratio of the aminated powder, the aqueous solution of glutaraldehyde and the aqueous solution of tannic acid being aminated powder: aqueous solution of glutaraldehyde: aqueous solution of tannic acid = 1:50:12; after the addition is completed, stirring is continued at constant temperature of 37° C. for 5 hours, and then solid-liquid separation is carried out, the solid phase is washed 3 times with deionized water, and dried at 60° C. for 5 hours to obtain the silica-based chelating agent.
[0027] Example 3
[0028] A nano-silica-based heavy metal soil remediation agent comprises a silica-based chelating agent, attapulgite, potassium dihydrogen phosphate and potassium humate, wherein the components are as follows by weight: 50 parts of silica-based chelating agent, 45 parts of attapulgite, 12 parts of potassium dihydrogen phosphate and 7 parts of potassium humate; the raw materials are uniformly mixed to obtain the soil remediation agent; wherein the preparation method of the silica-based chelating agent is as follows:
[0029] (1) preparing a dilute sodium hydroxide solution, wherein the mass percentage of sodium hydroxide in the dilute sodium hydroxide solution is 5%, and the solvent is water; adding cellulose and ethylene glycol to ethanol to prepare an alcohol suspension, wherein the mass ratio of cellulose and ethylene glycol added to ethanol to prepare the alcohol suspension is cellulose: ethylene glycol: ethanol = 7:8:50; stirring the alcohol suspension, and then adding the dilute sodium hydroxide solution to the alcohol suspension under stirring, wherein the volume ratio of the dilute sodium hydroxide solution added to the alcohol suspension is alcohol suspension: dilute sodium hydroxide solution = 1:1.4; continuing to stir for 3 hours after the addition is completed, and then separating the solid and the liquid, washing the solid phase with deionized water until the washed liquid is neutral, and drying at 60° C. for 5 hours to obtain pretreated cellulose;
[0030] (2) preparing an ethanol solution of tetraethyl orthosilicate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 6%, and the solvent is ethanol; adding the pretreated cellulose, glycine, and cyclohexane into deionized water to prepare a mixed solution, wherein the mass ratio of the pretreated cellulose, glycine, and cyclohexane added to the deionized water is pretreated cellulose: glycine: cyclohexane: deionized water = 4:0.2:7:100; heating the mixed solution to 60° C. in a water bath and then adding γ-aminoethylaminopropyl trimethoxysilane, after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 20 minutes, and then the ethanol solution of tetraethyl orthosilicate is added under stirring, and the volume ratio of γ-aminoethylaminopropyl trimethoxysilane and the ethanol solution of tetraethyl orthosilicate added to the mixed solution is mixed solution: γ-aminoethylaminopropyl trimethoxysilane: ethanol solution of tetraethyl orthosilicate = 30:2:100; after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 1 hour, solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and dried at 60° C. for 5 hours to obtain a silica-based powder;
[0031] (3) adding the silica-based powder to toluene, wherein the mass ratio of the silica-based powder to toluene is 1:50; stirring for 10 min to obtain a toluene suspension; heating the toluene suspension to 80° C. in a water bath to keep it warm, and then adding 3-aminopropyltriethoxysilane to the toluene suspension under stirring, wherein the volume ratio of the added 3-aminopropyltriethoxysilane to the toluene suspension is 0.4:50; after the addition is completed, stirring is continued at a constant temperature of 80° C. for 3 h, and condensation and reflux are performed during the constant temperature process; after the stirring is completed, solid-liquid separation is performed, the solid phase is washed with ethanol 3 times, and dried at 60° C. for 5 h to obtain an aminated powder;
[0032] (4) preparing an aqueous solution of tannic acid; in the aqueous solution of tannic acid, the concentration of tannic acid is 50 mg / mL, and the solvent is water; preparing an aqueous solution of glutaraldehyde, in the aqueous solution of glutaraldehyde, the mass percentage of glutaraldehyde is 6%, and the solvent is water; soaking the aminated powder in the aqueous solution of glutaraldehyde, heating it to 37° C. in a water bath, stirring at constant temperature for 2 hours, and then adding the aqueous solution of tannic acid under stirring, the mass ratio of the aminated powder, the aqueous solution of glutaraldehyde and the aqueous solution of tannic acid being aminated powder: aqueous solution of glutaraldehyde: aqueous solution of tannic acid = 2:50:14; after the addition is completed, stirring is continued at constant temperature of 37° C. for 5 hours, and then solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and dried at 60° C. for 5 hours to obtain the silica-based chelating agent.
[0033] Example 4
[0034] A nano-silica-based heavy metal soil remediation agent, comprising a silica-based chelating agent, attapulgite, potassium dihydrogen phosphate and potassium humate, wherein the components are as follows by weight: 50 parts of silica-based chelating agent, 50 parts of attapulgite, 14 parts of potassium dihydrogen phosphate and 8 parts of potassium humate; the raw materials are uniformly mixed to obtain the soil remediation agent; wherein the preparation method of the silica-based chelating agent is:
[0035] (1) preparing a dilute sodium hydroxide solution, wherein the mass percentage of sodium hydroxide in the dilute sodium hydroxide solution is 5%, and the solvent is water; adding cellulose and ethylene glycol to ethanol to prepare an alcohol suspension, wherein the mass ratio of cellulose and ethylene glycol added to ethanol to prepare the alcohol suspension is cellulose: ethylene glycol: ethanol = 7:10:50; stirring the alcohol suspension, and then adding the dilute sodium hydroxide solution to the alcohol suspension under stirring, wherein the volume ratio of the dilute sodium hydroxide solution added to the alcohol suspension is alcohol suspension: dilute sodium hydroxide solution = 1:1.5; continuing to stir for 3 hours after the addition is completed, and then separating the solid and liquid, washing the solid phase with deionized water until the washed liquid is neutral, and drying at 60° C. for 5 hours to obtain pretreated cellulose;
[0036] (2) preparing an ethanol solution of tetraethyl orthosilicate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 6%, and the solvent is ethanol; adding the pretreated cellulose, glycine, and cyclohexane into deionized water to prepare a mixed solution, wherein the mass ratio of the pretreated cellulose, glycine, and cyclohexane added to the deionized water is pretreated cellulose: glycine: cyclohexane: deionized water = 4:0.2:8:100; heating the mixed solution to 60° C. in a water bath and then adding γ-aminoethylaminopropyl trimethoxysilane, after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 20 minutes, and then the ethanol solution of tetraethyl orthosilicate is added under stirring, and the volume ratio of γ-aminoethylaminopropyl trimethoxysilane and the ethanol solution of tetraethyl orthosilicate added to the mixed solution is mixed solution: γ-aminoethylaminopropyl trimethoxysilane: ethanol solution of tetraethyl orthosilicate = 30:3:100; after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 1 hour, solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and dried at 60° C. for 5 hours to obtain a silica-based powder;
[0037] (3) adding the silica-based powder to toluene, wherein the mass ratio of the silica-based powder to toluene is 1:50; stirring for 10 min to obtain a toluene suspension; heating the toluene suspension to 80° C. in a water bath to keep it warm, and then adding 3-aminopropyltriethoxysilane to the toluene suspension under stirring, wherein the added volume of the 3-aminopropyltriethoxysilane and the volume ratio of the toluene suspension are 3-aminopropyltriethoxysilane: toluene suspension = 0.5:50; after the addition is completed, stirring is continued at a constant temperature of 80° C. for 3 h, and condensation and reflux are performed during the constant temperature process; after the stirring is completed, solid-liquid separation is performed, the solid phase is washed with ethanol 3 times, and dried at 60° C. for 5 h to obtain an aminated powder;
[0038] (4) preparing an aqueous solution of tannic acid; in the aqueous solution of tannic acid, the concentration of tannic acid is 50 mg / mL, and the solvent is water; preparing an aqueous solution of glutaraldehyde, in the aqueous solution of glutaraldehyde, the mass percentage of glutaraldehyde is 6%, and the solvent is water; soaking the aminated powder in the aqueous solution of glutaraldehyde, heating it to 37° C. in a water bath, stirring at constant temperature for 2 hours, and then adding the aqueous solution of tannic acid under stirring, the mass ratio of the aminated powder, the aqueous solution of glutaraldehyde and the aqueous solution of tannic acid being aminated powder: aqueous solution of glutaraldehyde: aqueous solution of tannic acid = 2:50:15; after the addition is completed, stirring is continued at constant temperature of 37° C. for 5 hours, and then solid-liquid separation is performed, the solid phase is washed with deionized water for 3 times, and dried at 60° C. for 5 hours to obtain the silica-based chelating agent.
[0039] Comparative Example 1
[0040] A comparative soil remediation agent includes a silica-based chelating agent, attapulgite, potassium dihydrogen phosphate and potassium humate, wherein the components are as follows by weight: 50 parts of silica-based chelating agent, 45 parts of attapulgite, 12 parts of potassium dihydrogen phosphate, and 7 parts of potassium humate; the raw materials are uniformly mixed to obtain a soil remediation agent; wherein the preparation method of the silica-based chelating agent is:
[0041] (1) preparing an ethanol solution of tetraethyl orthosilicate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 5%, and the solvent is ethanol; adding cellulose, glycine, and cyclohexane into deionized water to prepare a mixed solution, wherein the mass ratio of cellulose, glycine, and cyclohexane added to the deionized water is cellulose: glycine: cyclohexane: deionized water = 3:0.1:6:100; heating the mixed solution to 60° C. in a water bath and then adding γ-aminoethylaminopropyl trimethoxysilane under stirring; After the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 20 minutes, and then the ethanol solution of tetraethyl orthosilicate is added under stirring. The volume ratio of γ-aminoethylaminopropyltrimethoxysilane and the ethanol solution of tetraethyl orthosilicate added to the mixed solution is mixed solution: γ-aminoethylaminopropyltrimethoxysilane: ethanol solution of tetraethyl orthosilicate = 25:2:100; after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 1 hour, solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and dried at 60° C. for 5 hours to obtain a silica-based powder;
[0042] (2) adding the silica-based powder to toluene, wherein the mass ratio of the silica-based powder to toluene is 1:50; stirring for 10 min to obtain a toluene suspension; heating the toluene suspension to 80° C. in a water bath to keep it warm, and then adding 3-aminopropyltriethoxysilane to the toluene suspension under stirring, wherein the volume ratio of the added 3-aminopropyltriethoxysilane to the toluene suspension is 0.4:50; after the addition is completed, stirring is continued at a constant temperature of 80° C. for 3 h, and condensation and reflux are performed during the constant temperature process; after the stirring is completed, solid-liquid separation is performed, the solid phase is washed with ethanol 3 times, and dried at 60° C. for 5 h to obtain an aminated powder;
[0043] (3) preparing an aqueous solution of tannic acid; in the aqueous solution of tannic acid, the concentration of tannic acid is 40 mg / mL, and the solvent is water; preparing an aqueous solution of glutaraldehyde, in the aqueous solution of glutaraldehyde, the mass percentage of glutaraldehyde is 5%, and the solvent is water; soaking the aminated powder in the aqueous solution of glutaraldehyde, heating it to 37° C. in a water bath, stirring at constant temperature for 2 hours, and then adding the aqueous solution of tannic acid under stirring, the mass ratio of the aminated powder, the aqueous solution of glutaraldehyde and the aqueous solution of tannic acid being aminated powder: aqueous solution of glutaraldehyde: aqueous solution of tannic acid = 1:50:12; after the addition is completed, stirring is continued at constant temperature of 37° C. for 5 hours, and then solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and dried at 60° C. for 5 hours to obtain the silica-based chelating agent of this comparative example.
[0044] Comparative Example 2
[0045] A comparative soil remediation agent includes a silica-based chelating agent, attapulgite, potassium dihydrogen phosphate and potassium humate, wherein the components are as follows by weight: 50 parts of silica-based chelating agent, 45 parts of attapulgite, 12 parts of potassium dihydrogen phosphate, and 7 parts of potassium humate; the raw materials are uniformly mixed to obtain a soil remediation agent; wherein the preparation method of the silica-based chelating agent is:
[0046] (1) preparing a dilute sodium hydroxide solution, wherein the mass percentage of sodium hydroxide in the dilute sodium hydroxide solution is 5%, and the solvent is water; adding cellulose and ethylene glycol to ethanol to prepare an alcohol suspension, wherein the mass ratio of cellulose and ethylene glycol added to ethanol to prepare the alcohol suspension is cellulose: ethylene glycol: ethanol = 6:5:50; stirring the alcohol suspension, and then adding the dilute sodium hydroxide solution to the alcohol suspension under stirring, wherein the volume ratio of the dilute sodium hydroxide solution added to the alcohol suspension is alcohol suspension: dilute sodium hydroxide solution = 1:1.3; continuing to stir for 3 hours after the addition is completed, and then separating the solid and liquid, washing the solid phase with deionized water until the washed liquid is neutral, and drying at 60° C. for 5 hours to obtain pretreated cellulose;
[0047] (2) preparing an ethanol solution of tetraethyl orthosilicate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 5%, and the solvent is ethanol; adding the pretreated cellulose, glycine, and cyclohexane into deionized water to prepare a mixed solution, wherein the mass ratio of the pretreated cellulose, glycine, and cyclohexane added to the deionized water is pretreated cellulose: glycine: cyclohexane: deionized water = 3:0.1:6:100; heating the mixed solution to 60° C. in a water bath and then adding γ-aminoethylaminopropyl trimethoxysilane, after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 20 minutes, and then the ethanol solution of tetraethyl orthosilicate is added under stirring, and the volume ratio of γ-aminoethylaminopropyl trimethoxysilane and the ethanol solution of tetraethyl orthosilicate added to the mixed solution is mixed solution: γ-aminoethylaminopropyl trimethoxysilane: ethanol solution of tetraethyl orthosilicate = 25:2:100; after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 1 hour, solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and dried at 60° C. for 5 hours to obtain a silica-based powder;
[0048] (3) preparing an aqueous solution of tannic acid; in the aqueous solution of tannic acid, the concentration of tannic acid is 40 mg / mL, and the solvent is water; preparing an aqueous solution of glutaraldehyde, in the aqueous solution of glutaraldehyde, the mass percentage of glutaraldehyde is 5%, and the solvent is water; immersing the silica-based powder in the aqueous solution of glutaraldehyde, heating it to 37° C. in a water bath, stirring it at a constant temperature for 2 hours, and then adding the aqueous solution of tannic acid under stirring, the mass ratio of the silica-based powder, the aqueous solution of glutaraldehyde and the aqueous solution of tannic acid being silica-based powder: aqueous solution of glutaraldehyde: aqueous solution of tannic acid = 1:50:12; after the addition is completed, stirring is continued at a constant temperature of 37° C. for 5 hours, and then solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and dried at 60° C. for 5 hours to obtain the silica-based chelating agent described in this comparative example.
[0049] Comparative Example 3
[0050] A comparative soil remediation agent includes a silica-based chelating agent, attapulgite, potassium dihydrogen phosphate and potassium humate, wherein the components are as follows by weight: 50 parts of silica-based chelating agent, 45 parts of attapulgite, 12 parts of potassium dihydrogen phosphate, and 7 parts of potassium humate; the raw materials are uniformly mixed to obtain a soil remediation agent; wherein the preparation method of the silica-based chelating agent is:
[0051] (1) preparing a dilute sodium hydroxide solution, wherein the mass percentage of sodium hydroxide in the dilute sodium hydroxide solution is 5%, and the solvent is water; adding cellulose and ethylene glycol to ethanol to prepare an alcohol suspension, wherein the mass ratio of cellulose and ethylene glycol added to ethanol to prepare the alcohol suspension is cellulose: ethylene glycol: ethanol = 6:5:50; stirring the alcohol suspension, and then adding the dilute sodium hydroxide solution to the alcohol suspension under stirring, wherein the volume ratio of the dilute sodium hydroxide solution added to the alcohol suspension is alcohol suspension: dilute sodium hydroxide solution = 1:1.3; continuing to stir for 3 hours after the addition is completed, and then separating the solid and liquid, washing the solid phase with deionized water until the washed liquid is neutral, and drying at 60° C. for 5 hours to obtain pretreated cellulose;
[0052] (2) preparing an ethanol solution of tetraethyl orthosilicate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 5%, and the solvent is ethanol; adding the pretreated cellulose, glycine, and cyclohexane into deionized water to prepare a mixed solution, wherein the mass ratio of the pretreated cellulose, glycine, and cyclohexane added to the deionized water is pretreated cellulose: glycine: cyclohexane: deionized water = 3:0.1:6:100; heating the mixed solution to 60° C. in a water bath and then adding γ-aminoethylaminopropyl trimethoxysilane, after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 20 minutes, and then the ethanol solution of tetraethyl orthosilicate is added under stirring, and the volume ratio of γ-aminoethylaminopropyl trimethoxysilane and the ethanol solution of tetraethyl orthosilicate added to the mixed solution is mixed solution: γ-aminoethylaminopropyl trimethoxysilane: ethanol solution of tetraethyl orthosilicate = 25:2:100; after the addition is completed, the mixture is stirred at a constant temperature of 60° C. for 1 hour, solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and dried at 60° C. for 5 hours to obtain a silica-based powder;
[0053] (3) Add the silica-based powder to toluene, the mass ratio of the silica-based powder to toluene is silica-based powder: toluene = 1:50; stir for 10 minutes to obtain a toluene suspension; heat the toluene suspension to 80°C in a water bath and keep it warm, then add 3-aminopropyltriethoxysilane to the toluene suspension under stirring, the volume ratio of the added 3-aminopropyltriethoxysilane to the toluene suspension is 3-aminopropyltriethoxysilane: toluene suspension = 0.4:50; continue to stir at a constant temperature of 80°C for 3 hours after the addition is completed, and condense and reflux during the constant temperature process; after the stirring is completed, separate the solid and liquid, wash the solid phase with ethanol 3 times, and dry it at 60°C for 5 hours to obtain the silica-based chelating agent described in this comparative example.
[0054] Example 5
[0055] The contaminated test soil was selected, and the effective lead content in the test soil was measured to be 1035 mg / kg, and the effective arsenic content was 16.02 mg / kg. The soil remediation agents prepared by the methods described in the above embodiments and comparative examples were mixed evenly with the contaminated test soil, and the mixing weight ratio was soil remediation agent: contaminated test soil = 1:100; water was added to make the water content 70% (mass fraction), and cultivated at room temperature for 90 days, turning over and replenishing water once a day, so that the water content was maintained at 70% (mass fraction). After cultivation, the effective lead content and effective arsenic content in each group of soil were tested, and the results are shown in Table 1.
[0056] As shown in Table 1, the soil remediation agent prepared by the method of the present invention has a good remediation effect on the polluting elements lead and arsenic in the soil, and can significantly reduce the content of effective lead and effective arsenic, and reduce the toxicity of pollutants to the soil. The present invention first treats cellulose with alkali solution to reduce the crystallinity and polymerization degree of cellulose, improve the dispersibility, and form a large number of hydroxyl groups on the surface of cellulose, and then form a composite powder of nano-silica-cellulose. On the one hand, the specific surface area and porosity of the matrix powder are increased, and the adsorption of the material is improved. On the other hand, macromolecular groups and active functional groups are formed on the surface of the matrix powder, which improves the chelation of the matrix and facilitates the subsequent further modification of the powder. Afterwards, 3-aminopropyltriethoxysilane is used to convert the hydroxyl groups on the surface of the powder into amino groups, and then tannic acid modification is performed, which can significantly improve the chelation of the silica-based chelating agent to the polluting ions, form a stable chelate, reduce the content of free polluting ions in the soil, and play a role in soil remediation.
[0057] Table 1
[0058] Experimental Group Effective lead content (mg / kg) Available arsenic content (mg / kg) Example 1 329 5.83 Example 2 306 5.68 Example 3 312 5.75 Example 4 320 5.86 Comparative Example 1 511 7.03 Comparative Example 2 437 6.21 Comparative Example 3 664 8.90
[0059] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A nano-silica-based heavy metal soil remediation agent, characterized in that: The invention comprises a silicon dioxide-based chelating agent, attapulgite, potassium dihydrogen phosphate and potassium humate, wherein the preparation method of the silicon dioxide-based chelating agent is as follows: (1) preparing a dilute sodium hydroxide solution; adding cellulose and ethylene glycol to ethanol to prepare an alcohol suspension, stirring the alcohol suspension, and then adding the dilute sodium hydroxide solution to the alcohol suspension under stirring, continuing to stir for more than 3 hours after the addition is completed, and then separating the solid and the liquid, washing the solid phase with deionized water until the washed liquid is neutral, and drying at 60±5° C. for more than 5 hours to obtain pretreated cellulose; (2) preparing an ethanol solution of tetraethyl orthosilicate; adding the pretreated cellulose, glycine, and cyclohexane into deionized water to prepare a mixed solution, heating the mixed solution to 60±5° C. in a water bath, and then adding γ-aminoethylaminopropyltrimethoxysilane under stirring. After the addition is completed, stirring is carried out at a constant temperature of 60±5° C. for 20 to 30 minutes. Then, the ethanol solution of tetraethyl orthosilicate is added under stirring. After the addition is completed, stirring is carried out at a constant temperature of 60±5° C. for more than 1 hour, solid-liquid separation is performed, the solid phase is washed with deionized water for more than 3 times, and dried at 60±5° C. for more than 5 hours to obtain a silica-based powder; (3) adding the silica-based powder to toluene and stirring for more than 10 minutes to obtain a toluene suspension; heating the toluene suspension in a water bath to 80±5° C. for insulation, then adding 3-aminopropyltriethoxysilane to the toluene suspension under stirring, and continuing to stir at a constant temperature of 80±5° C. for more than 3 hours after the addition is completed, condensing and refluxing during the constant temperature process; after the stirring is completed, the solid-liquid separation is completed, the solid phase is washed with ethanol for more than 3 times, and dried at 60±5° C. for more than 5 hours to obtain an aminated powder; (4) preparing an aqueous solution of tannic acid; preparing an aqueous solution of glutaraldehyde, immersing the aminated powder in the aqueous solution of glutaraldehyde, heating in a water bath to 37±3° C., stirring at a constant temperature for more than 2 hours, and then adding the aqueous solution of tannic acid under stirring. After the addition is completed, continue to stir at a constant temperature of 37±3° C. for more than 5 hours, then separate the solid and liquid, wash the solid phase with deionized water for more than 3 times, and dry at 60±5° C. for more than 5 hours to obtain the silica-based chelating agent.
2. A nano-silica-based heavy metal soil remediation agent according to claim 1, characterized in that: The components of the nano-silica-based heavy metal soil remediation agent are calculated by weight as follows: 50 parts of silica-based chelating agent, 40-50 parts of attapulgite, 10-14 parts of potassium dihydrogen phosphate, and 6-8 parts of potassium humate.
3. A nano-silica-based heavy metal soil remediation agent according to claim 1, characterized in that: In the step (1), the mass percentage of sodium hydroxide in the dilute sodium hydroxide solution is 5% to 6%, and the solvent is water; the mass ratio of cellulose and ethylene glycol added to ethanol to form an alcohol suspension is cellulose:ethylene glycol:ethanol=6-7:2-10:50; the volume ratio of adding the dilute sodium hydroxide solution to the alcohol suspension is alcohol suspension:dilute sodium hydroxide solution=1:1.2-1.
5.
4. A nano-silica-based heavy metal soil remediation agent according to claim 1, characterized in that: In the step (2), in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 5% to 6%, and the solvent is ethanol; the mass ratio of the pretreated cellulose, glycine, and cyclohexane added to deionized water is pretreated cellulose: glycine: cyclohexane: deionized water = 3 to 4: 0.1 to 0.2: 5 to 8: 100; the volume ratio of γ-aminoethylaminopropyltrimethoxysilane and the ethanol solution of tetraethyl orthosilicate added to the mixed solution is mixed solution: γ-aminoethylaminopropyltrimethoxysilane: ethanol solution of tetraethyl orthosilicate = 25 to 30: 1 to 3:
100.
5. A nano-silica-based heavy metal soil remediation agent according to claim 1, characterized in that: In the step (3), the mass ratio of the silica-based powder added to toluene is silica-based powder: toluene = 1:50-100; the volume ratio of the added 3-aminopropyltriethoxysilane to the toluene suspension is 3-aminopropyltriethoxysilane: toluene suspension = 0.3-0.5:
50.
6. A nano-silica-based heavy metal soil remediation agent according to claim 1, characterized in that: In the step (4), the concentration of tannic acid in the aqueous solution of tannic acid is 40-50 mg / mL, and the solvent is water; the mass percentage of glutaraldehyde in the aqueous solution of glutaraldehyde is 5%-6%, and the solvent is water; the mass ratio of the aminated powder, the aqueous solution of glutaraldehyde and the aqueous solution of tannic acid is aminated powder: aqueous solution of glutaraldehyde: aqueous solution of tannic acid = 1-2:50:10-15.